2022
DOI: 10.1080/02724634.2022.2162909
|View full text |Cite
|
Sign up to set email alerts
|

The extinct shark, Ptychodus (Elasmobranchii, Ptychodontidae) in the Upper Cretaceous of central-western Russia—The road to easternmost peri-Tethyan seas

Abstract: Isolated teeth belonging to the genus Ptychodus Agassiz, 1834 (Chondrichthyes; Elasmobranchii) from the Upper Cretaceous of the Ryazan and Moscow Oblast regions (European Russia) are described and discussed in detail herein. The taxonomic composition of the Ptychodus assemblage from the Ryazan region is very diverse including the first records of the cuspidate species P. altior and P. anonymus, which thus is largely consistent with those from other contemporaneous European localities. Ptychodus ubiquitously in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 103 publications
1
14
0
2
Order By: Relevance
“…Geographic and stratigraphic occurrences of Ptychodus are based on Amadori et al (2022b) and updated with the Ukrainian records reported in the present paper. Data on the occurrences of the possible prey of Ptychodus (ammonites, inoceramids and decapods) were obtained from the Paleobiology Database (PaleoDB, https://paleobiodb.org/ downloaded on 13/03/2023; see also Uhen, 2018 ) and updated when possible (see also Table S2 in online supplementary data).…”
Section: Methodsmentioning
confidence: 88%
See 1 more Smart Citation
“…Geographic and stratigraphic occurrences of Ptychodus are based on Amadori et al (2022b) and updated with the Ukrainian records reported in the present paper. Data on the occurrences of the possible prey of Ptychodus (ammonites, inoceramids and decapods) were obtained from the Paleobiology Database (PaleoDB, https://paleobiodb.org/ downloaded on 13/03/2023; see also Uhen, 2018 ) and updated when possible (see also Table S2 in online supplementary data).…”
Section: Methodsmentioning
confidence: 88%
“…Among them, one of the most speciose is the enigmatic, extinct shark Ptychodus . Its remains have been recovered from Cretaceous deposits of all continents except Antarctica ( Woodward, 1912 ; Herman, 1977 ; Siverson, 1999 ; Cappetta, 2012 ; Hamm, 2020 ; Amadori et al, 2022b ). Within the genus Ptychodus , two groups characterized by cuspidate and un-cuspidate teeth respectively can be distinguished based on tooth morphologies (e.g., Cappetta, 2012 ; Shimada, 2012 ; Amadori et al, 2019a , b , 2020a , b ; Hamm, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Potential causes underlying the species decline and subsequent demise of Strophodus remain elusive but are likely to be multifactorial, perhaps involving both fluctuations in the relative availability of preferred food resources (note that marine hard-shelled invertebrates declined across the Jurassic/Cretaceous boundary; see Tennant et al, 2017, and references therein) and an increasing competitive overlap with crown group elasmobranchs (i.e., sharks and rays), which rapidly diversified during the Jurassic and Cretaceous (Guinot & Cavin, 2016;Kriwet et al, 2009;Underwood, 2006). Interestingly, the final demise of Strophodus coincides with the appearance of the giant durophagous shark Ptychodus Agassiz, 1834 (see Cappetta, 2012, andreferences therein), which quickly diversified into many different species soon after it first appeared during the Albian to become the most dominant Cretaceous durophagous predator to have ever lived (e.g., Shimada et al, 2009Shimada et al, , 2010Amadori et al, 2020Amadori et al, , 2022Amadori et al, , 2023Jambura & Kriwet, 2020). This suggests that Ptychodus might have benefitted from the freed ecospace that was left in the wake of Strophodus' extinction.…”
Section: Palaeoecology and Distribution Of Strophodusmentioning
confidence: 99%
“…Two species groups, which often co-occur with each other, can be distinguished: species with low-crowned (uncuspidate) teeth and species with high-crowned (cuspidate) teeth, such as Ptychodus decurrens and P. mammillaris, respectively (e.g. [8,10]). Teeth were arranged in a way that they formed large dental plates supported by elongated, V-shaped jaws [1,8,9,[11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…105 to 75 million years old) marine deposits of all continents except Antarctica (e.g. [1][2][3][4][5][6][7][8][9][10]). This diverse Cretaceous genus, including at least 16 species, is primarily known from isolated teeth and partial dentitions.…”
Section: Introductionmentioning
confidence: 99%